Non-pharmacologic Approaches in Preoperative Anxiety, a Comprehensive Review - Wang, Rulin; Huang, Xin; Wang, Yuan; Akbari, Masod (Frontiers in Public Health, 2022)
During the pre-operation period, surgical candidates experience situations that stimulate psychological anxiety leading to stress during and after surgery which is known as preoperative anxiety. This condition can cause psychological and physiological adverse effects on both children and adults. Due to the high prevalence and adverse effects of preoperative anxiety, different treatments have been evaluated including pharmacological and non-pharmacological approaches. As pharmacological treatments may cause adverse effects such as breathing problems, drowsiness, interfering with anesthetic drugs, and prolonged recovery, non-pharmacological interventions are becoming more popular. These methods include cognitive-behavioral therapy, music therapy, pre-op preparation video, aromatherapy, hypnosis, guided imagery relaxation therapy, and massage. In this study, the most popular non-pharmacological approaches to preoperative anxiety are reviewed focusing on more recent evidence provided by clinical studies. The reviewed clinical evidence on the mentioned methods shows the efficacy of non-pharmacological interventions for the treatment of preoperative anxiety, so they can be used in patients of different ages and types of disease and surgery.